A Study on Representation of Women’s Supremacy in Contemporary Tamil Movies - Nirmala, M.; Mohamed, S.H. Sheik; Mukit, Abdul (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
Women’s Supremacy, women's liberation, the empowerment of women, and gender equality are frequently discussed concepts in modern India. The film industry, among other stakeholders, is taking steps to contribute to women’s empowerment. In India, the film industry is seeking to change society by touching on topics that are rarely discussed in public. Present-day directors have begun to give greater visibility to the difficulties women face. There is a new wave of women-centric movies that is bringing about a quiet rebellion in India. This article reveals how women’s supremacy is portrayed in select Tamil movies.